How does the social distance between an employee and a manager affect employee competition for a reward? - Glenn Dutcher (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2011)
This study examines how employees internalize differences in social distance between themselves and their managers when they are competing for a reward given by the manager. In an employer/employee relationship, this difference in social distance between the employer and the various employees leads to a disadvantageous situation for the socially distant workers when raises, promotions, special considerations etc. are given. Since social distance is present in most organizations, understanding how employees work effort changes in response to changes in social distance is of upmost importance. In prior literature, this disadvantage has always been assumed/shown to lead to lower effort than the advantaged worker. The results partially back up this claim and show that females who are socially distant from their manager contribute much less than females who are socially closer or males regardless of the social distance.
Keywords: C91; C92; 330; Experiment; Social distance; Angestellte; Leistungsanreiz; Hierarchie; Führungskräfte; Test; Ohio